Lessons learned from early compassionate use of convalescent plasma on critically ill patients with Covid‐19 - Liu, Miao; Chen, Zhen; Dai, Meng‐Yuan; Yang, Jun‐Hui; Chen, Xiao‐Bing; Chen, Di; You, Hua; Guo, Xin; Leng, Yan; Yu, Li; Zhang, Meng‐Li; Wu, Xian; et al. (Transfusion (Philadelphia, Pa.), 2020)
Background The management of critically ill patients with coronavirus disease 2019 (COVID‐19), caused by a new human virus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is challenging. Recently, there have been several reports with inconsistent results after treatment with convalescent plasma (CP) on critically ill patients with COVID‐19, which was produced with a neutralizing antibody titer and tested in a P3 or P4 laboratory. However, due to the limitation of the conditions on mass production of plasma, most producers hardly had the capability to isolate the neutralizing antibody. Here, we report the clinical courses of three critically ill patients with COVID‐19 receiving CP treatments by total immunoglobulin G (IgG) titer collection. Methods Three patients with COVID‐19 in this study were laboratory confirmed to be positive for SARS‐CoV‐2, with radiographic and clinical features of pneumonia. CP was collected by total IgG titer of 160 (range, 200‐225 mL), and patients were transfused between 20 and 30 days after disease onset at the critical illness stage as a trial in addition to standard care. The clinical courses of these patients, including laboratory results and pulmonary functional and image studies after receiving convalescent plasma infusions, were reviewed. Results No therapeutic effect of CP was observed in any of the patients; instead, all three patients deteriorated and required extracorporeal membrane oxygenation treatment. A potential cytokine storm 4 hours after infusion of CP in Patient 2 was observed. No more patients were put on the trial of CP transfusion. Conclusions We recommend extreme caution in using CP in critically ill patients more than 2 weeks after the onset of COVID‐19 pneumonia.